"Je suis Satisfaction:" Russian politics in the age of hybrid media. Issue 1 (2nd January 2020) - Ryabovolova, Alina; Hemment, Julie
ABSTRACT: This article traces a hybrid media event that unfolded in Russia in January 2018. Started on YouTube as a homoerotic music video, the so-called Satisfaction Challenge turned into a meme with hundreds of participants, millions of followers, and national media coverage. Using digital ethnography, we examine the interaction of Russian officials, publics, and media throughout this multi-sited, multi-actor, and multi-voiced event. In so doing, we pose questions about the relationship between hybrid media and political regimes, particularly, the interplay between traditional and digital media as it plays out in the realm of social contention in Russia.